Pengaruh Bahan Pengikat Gelatin dalam Formula Tablet Ekstrak Daun Kemuning (Murraya paniculata (L.) Jack) secara Granulasi Basah - Yeni Fitriana; Titik Sunarni; Widodo Priyanto (Fakultas Farmasi Universitas Setia Budi, 2010)
Kemuning (Murraya paniculata (L.) Jack) is one of Indonesia medicine plants. Kemuning leaves can be used to decrease cholesterol. The experiment was aimed to make tablets of kemuning leaves extract with gelatin as binding agent that fulfilled the requirements of tablet’s physical quality. Extract of kemuning leaves was obtained from kemuning leaves powder by maceration method using ethanol 70%. The obtained extract was soaked for several days and then evaporated till thick extract was obtained. Kemuning leaves extract tablets were made in 3 formulation with difference concentrations of binding agent, i.e. formula I contained 1% of gelatin mucilage 5%, formula II contained 2% and formula III contained 3%. The method used to make tablets of kemuning leaves extract was wet granulation method. The obtained granules were physically tested in cluding flowing time, the angle of repose, and loss on drying. The obtained tablets were physically tested including weight homogeneity, hardness, friability and disintegration time. The obtained data was statistically analyzed using SPSS 11.0 for windows program i.e. one way anova added with one factor at 95% convidence. The conclusion of the experiment was that kemuning leaves extract could be made tablets that fulfilled therequirement of tablet’s physical quality. The result of the experiment showed that the three formulations produced tablets with weight homogeneity, hardness, friability and disintegration time that fulfilled the requirement of good physical quality of tablet.